La problématique du stockage des déchets ménagers et assimilés face au changement d'échelle de planification en Région Île-de-France - Rym Mtibaa; Jacques Mery; André Torre (Développement Durable et Territoires)
The management of the waste of the Ile-de-France region is an interesting case study for analysing causes and effects of a scale change on territorial governance: eight local plans have been recently renewed for a unique regional plan. The reasons of this change and the consequences on the landfilling of non-dangerous waste (a typically controversial application of territorial governance) are presented and analyzed in the paper. The change of scale does not modify the fundamentals of regional waste landfilling, but allows for an adequate institutional frame.